Hubungan Loneliness dengan College Belongingness pada Mahasiswa saat Pandemi Covid-19 - Najla Rizky Firyal; Eni Nuraeni Nugrahawati (UNISBA Press, 2021)
Abstract. The Covid-19 pandemic has made the implementation of Distance Learning (PJJ) in Indonesia no exception for students. Establishing relationships is one of the requirements so that the adaptation process of students on campus becomes easier. By fulfilling the needs of students in establishing relationships, it will bring up college belongingness to students. Students with high college belongingness are less likely to experience psychological problems such as loneliness. The purpose of this study was to see the close relationship between loneliness and college belongingness to students in Bandung during the Covid-19 pandemic. The research subjects were 400 students in Bandung. The measuring instrument used in this study is UCLA Loneliness Scale version 3 by D.W. Russel (1996) which was adapted by Distiyan (2020), and the measuring instrument of G. Arslan's College Belongingness Questionnaire (2020) which has been adapted to Indonesian. Based on data analysis using Spearman's rank, it was found that there was a negative relationship between loneliness and college belongingness with a low level of closeness. Abstrak. Pandemi Covid-19 membuat diberlakukannya Pembelajaran Jarak Jauh (PJJ) di Indonesia tidak terkecuali pada mahasiswa. Menjalin relasi menjadi salah satu kebutuhan supaya proses adaptasi mahasiswa di kampus menjadi lebih mudah. Dengan terpenuhinya kebutuhan mahasiswa dalam menjalin relasi akan memunculkan college belongingness pada mahasiswa. Mahasiswa dengan college belongingness tinggi akan lebih sedikit untuk mengalami masalah psikologis seperti loneliness. Tujuan penelitian ini untuk melihat keeratan hubungan antara loneliness dengan college belongingness pada mahasiswa di Kota Bandung saat Pandemi Covid-19. Subjek penelitian sebanyak 400 mahasiswa di Kota Bandung. Alat ukur yang digunakan dalam penelitian ini adalah UCLA Loneliness Scale version 3 milik D.W. Russel (1996) yang diadaptasi oleh Distiyan (2020), dan alat ukur College Belongingness Questionnaire milik G. Arslan (2020) yang sudah diadaptasi ke Bahasa Indonesia. Berdasarkan analisis data dengan menggunakan rank Spearman, diperoleh hasil terdapat hubungan negatif antara loneliness dengan college belongingness dengan tingkat keeratan yang rendah.